Prime-boost strategies for malaria vaccine development. - Dunachie, S; Hill, A (2003)
Malaria is an intracellular pathogen, for which an effective vaccine is likely to require induction of cell-mediated immunity. Immunisation approaches that stimulate strong and persistent levels of effector T-cells are being sought by many researchers. DNA vaccines, recombinant protein and viral vectors were amongst the vaccine delivery systems that appeared promising for the generation of cellular immunity, and in some initial studies in small animals this goal was achieved. However, clinical trials of these candidate vaccines when used alone or in repeated homologous boosting regimes have been disappointing, with short-lived low levels of induced specific T-cell responses. Recent years have seen the development of immunisation strategies using a combination of different antigen delivery systems encoding the same epitopes or antigen, delivered at an interval of a few weeks apart. This sequential immunisation approach with different vectors is known as heterologous prime-boosting and is capable of inducing greatly enhanced and persistent levels of CD8+ T-cells and Th1-type CD4+ T-cells compared to homologous boosting. This review will summarise the key pre-clinical studies of prime-boost strategy and outline recent progress in clinical trials of this approach. Possible mechanisms of action and potential improvements to existing delivery systems will be discussed. The prime-boost approach represents an encouraging step towards establishing an effective preventative vaccine to one of the world's greatest killers.